NEPA and climate change: consideration of climate mitigation and adaptation in infrastructure review processes. (1st March 2022) - Ulibarri, Nicola; Han, David
Abstract: Addressing climate change requires a shift in the planning, design, and operations of infrastructure. Reducing greenhouse gas emissions will require decarbonizing energy, water, transportation, and other infrastructures. And the long-term resilience of many infrastructure projects will be affected by expected changes in precipitation, sea level, heat and cold spells, and natural hazards like hurricanes and wildfires. Many scholars and practitioners have suggested that environmental impact assessment (EIA)—a required review of the environmental impacts of infrastructure projects—can serve as an opportunity to encourage infrastructure to be more climate friendly. In the United States (like many other jurisdictions), federal agencies are not required to address climate change in EIA reviews, but guidance from the Council on Environmental Quality advises them to consider greenhouse gas emissions and the effects of climate change. This paper applied qualitative content analysis to assess integration of climate change into environmental impact statements (EISs) in the United States. We found that most EISs included some consideration of climate change, most frequently with a few brief mentions rather than extensive integration. We also found more focus on climate mitigation than adaptation, in both recognizing potential impacts and managing those impacts. Surprisingly, infrastructure that is more directly related to climate change—water and energy infrastructure, as well as land management—had lower overall climate integration than transportation, information technology, or buildings and operations. As exploratory work, this research suggests that federal agencies could do more to mitigate greenhouse gas emissions in approved projects and in particular to make infrastructure more adaptive to climate change. The work also raises a number of questions as to whether EIA is the right regulatory tool to encourage climate friendly infrastructure.